2021
DOI: 10.18502/ijm.v13i2.5983
|View full text |Cite
|
Sign up to set email alerts
|

Exploring clinically isolated Staphylococcus sp. bacteriocins revealed the production of amonabactin, micrococcin, and α-circulocin

Abstract: Background and Objectives: Bacteriocins are considered alternative non-conventional antimicrobials produced by certain bacteria with activity against closely related species. The present study focuses on screening, characterization, and partial purification of bacteriocins produced by Staphylococcus sp. isolated from different clinical sources such as pus and blood. Materials and Methods: A total of 100 Staphylococcus isolates were screened for bacteriocin production using spot on lawn assay and agar dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…This study screened a bank of CoNS against clinical isolates of MRSA in an at tempt to identify antimicrobial producers with activity against this specific pathogen Twenty-one MRSA isolates were used to reduce the likelihood that natural variations in antimicrobial susceptibility amongst the S. aureus strains would result in a putative anti microbial producer being overlooked. Unlike many other bacteriocin investigations which screen CoNS against a broad range of indicators or a specific sensitive indicato during the preliminary testing [36,[38][39][40], this investigation took a more directed ap proach with a single target pathogen in mind.…”
Section: Discussionmentioning
confidence: 99%
“…This study screened a bank of CoNS against clinical isolates of MRSA in an at tempt to identify antimicrobial producers with activity against this specific pathogen Twenty-one MRSA isolates were used to reduce the likelihood that natural variations in antimicrobial susceptibility amongst the S. aureus strains would result in a putative anti microbial producer being overlooked. Unlike many other bacteriocin investigations which screen CoNS against a broad range of indicators or a specific sensitive indicato during the preliminary testing [36,[38][39][40], this investigation took a more directed ap proach with a single target pathogen in mind.…”
Section: Discussionmentioning
confidence: 99%
“…Using our collection of nasal staphylococcal isolates, we identified the S. aureus strain D4-19 with a plasmid carrying the MP1 BGC. A number of studies have identified MP1 BGCs in a variety of staphylococcal species, including S. aureus ( 34 ), S. epidermidis ( 35 ), Staphylococcus equorum ( 36 ), Staphylococcus pseudintermedius ( 37 ), Staphylococcus agnetis , and S. hominis ( 20 ). Also, an isolate from Mammaliicoccus sciuri (formerly Staphylococcus sciuri ) ( 38 ) has been shown to produce MP1.…”
Section: Discussionmentioning
confidence: 99%
“…Using our collection of nasal staphylococcal isolates, we identified the S. aureus strain D4-19 carrying a plasmid encoding the MP1 BGC. A number of studies have identified MP1-BGCs in a variety of staphylococcal species, including S. aureus (32), S. epidermidis (33), Staphylococcus equorum (34), Staphylococcus pseudintermediu s (35), Staphylococcus agnetis , and S. hominis (19). Also, an isolate from Mammaliicoccus sciuri (former Staphylococcus sciuri ) (36) has been shown to produce MP1.…”
Section: Discussionmentioning
confidence: 99%